Assessment of Heat Transfer Characteristics of a Latent Heat Thermal Energy Storage System: Multi Tube Design. (February 2019) - Sodhi, Gurpreet Singh; Vigneshwaran, K.; Jaiswal, Abhishek Kumar; Muthukumar, P
Abstract: In this study, a numerical investigation of heat and mass transfer characteristics of a high temperature phase change material (PCM) is presented. The phase change material used is Sodium Nitrate with a melting point of 306 °C. For a fixed PCM mass, investigations are carried out on a multi-tube heat exchanger system for examining the effects of tube size and number of tubes on overall heat transfer rate. The performance of latent heat storage system during the charging and discharging processes are discussed. Further, the results are elaborated for three multi-tube systems to optimize the number of tubes to be used with the constant heat transfer surface area. The natural convection pattern during charging is observed with the help of temperature contours and streamlines. The solidification front pattern of the PCM, during the discharging process is visualized through melt fraction contours. With the increase in the number of tubes from 13 to 25, the heat distribution throughout the storage system is very effective which lead to reduction in charging and discharging times by 20% and 48% respectively.